4-H Project Learning - Judith Levings (EDIS, 2014)
A project is a planned series of learning experiences of six hours or more within a particular area of youth interest (Florida 4-H definition). The purpose of a 4-H project is to promote mastery of subject matter and to foster life skill development. This 4-page fact sheet was written by Judith Levings and published by the UF Department of 4-H Youth Development, August 2014.